A Model Proposal for the Flood Risk Analysis of the Architectural Heritage: Edirne Bayezid II Complex Flood Risk Analysis - Erdogan, Banu Gokmen; Unal, Zeynep Gul (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2021)
According to the climate change projections, there will be an increase in torrential rains and related floods. In parallel with this, the risk of flood damage to the architectural heritage will increase in the future. Floods cause serious damage to the architectural heritage. Since flood risk analyses are generally made basin-based, studies on flood risks of cities are still inadequate. Therefore, flood risks arising from the architectural heritage's own characteristics and its current situations are not known. Not knowing which architectural heritage poses the flood risk and its potential losses increase the damage. In preventive preservation, the measures taken before the risks occur are effective in reducing the damage, even if they do not eliminate the risks completely. It is necessary to know the flood risk in order to make the architectural heritage be prepared against floods that are predicted to increase with the effect of climate change. This study is aimed to develop a model for analysing the flood risk of architectural heritage. With the Architectural Heritage Flood Risk Analysis Model (MISRAM) developed in line with this purpose, the vulnerability of any architectural heritage can be calculated with the parameter scores developed over the building's own characteristics and current state. The development and implementation of the model were carried out in 4 stages. In the first stage: flood damage in the architectural heritage has been investigated. On-site detection, observation, and investigations were made to determine the factors that increase the damage. Flood-induced forces and effects from the data obtained. The types of damage caused by these forces and effects in the architectural heritage, the areas where the damage occurred in the building and the possible damage risks were determined. In the second stage: the factors affecting the damage level were defined and transformed into flood risk parameters. In the third stage: the flood risk parameters and the coefficient of flood risk area were made into a calculation table in an Excel program. The analyse form was created by adding the building identification section to the created calculation sheet. In the fourth stage: the risk analysis forms were filled in on-site. As a result of the researches made in the scope of the study's problem, the findings below have been reached: Climate change causes an increase in sudden and heavy rains and accordingly flash floods, and these effects will continue to increase in the future. Architectural heritage located in the region with the same flood risk coefficient may have different flood risk levels depending on different parameters. Therefore, the flood risk of the architectural heritage cannot be calculated only through the flood risk of the region where it is located, a heritage-specific risk analysis model should be developed and in this model, the heritage's own characteristics and current situation should be taken into account. Factors that increase flood damage in architectural heritage should be identified and included in the calculation in risk analysis. There has been an increase in the number of floods in the province of Edirne after the 2000s. The developed model proposal MISRAM was applied to the buildings of Bayezid II Complex, and the flood risk levels of the buildings were determined. Determining the flood risk level in the flood management planning of the architectural heritage is the first step and constitutes important data for decision-makers. In further studies, it is recommended to develop protection measures and interventions that will not adversely affect the heritage values for the architectural heritage whose flood risk level is determined, and to analyse the flood risk of the cultural heritage other than the architectural heritage. The flood risk of the architectural heritage can be analysed and appropriate flood prevention and response decisions can be made via applying MISRAM. It can be integrated into disaster management plans of local governments, and it may constitute the first step in reducing architectural heritage damages and preventing losses in flood disasters. MISRAM is a method that can be used both as a resource for creating architectural heritage flood risk maps and for decision-makers to take appropriate measures and intervention decisions.
Keywords: Architectural heritage flood risk analysis; climate change; Edirne Bayezid II Complex; flood hazard on architectural heritage; CULTURAL-HERITAGE; AYUTTHAYA; IMPACTS; Architecture